Synthesis and Sympatholytic and Adrenomimetic Activities of Amino Amides and Amino Esters Based on 1-(1,3-Benzodioxol-5-yl)cyclopentane- and 4-(1,3-Benzodioxol-5-yl)tetrahydro-2H-pyran-4-carboxylic Acids - Margaryan, R. E.; Stepanyan, G. V.; Aghekyan, A. A.; Panosyan, H. A.; Arutyunyan, S. A.; Tsatinyan, A. S.; Grigoryan, M. S.; Mkryan, G. G. (Russian journal of organic chemistry, 2025)
The reactions of 2-(1,3-benzodioxol-5-yl)acetonitrile with 1,4-dibromobuthane and 2,2′-bis(2-chloroethyl) ether gave 1-(1,3-benzodioxol-5-yl)cyclopentane- and 4-(1,3-benzodioxol-5-yl)tetrahydro-2 H -pyran-4-carbonitriles which were hydrolyzed in alkaline medium to the corresponding carboxylic acids, and the latter were converted to acid chlorides. 1-(1,3-Benzodioxol-5-yl)cyclopentane- and 4-(1,3-benzodioxol-5-yl)tetrahydro-2 H -pyran-4-carbonyl chlorides reacted with N , N -dialkylaminoalkyl- and hetarylalkylamines, as well as with N , N -dialkylaminoalkanols and hetarylalkanols, to afford the target (1,3-benzodioxol-5-yl)cyclopentane(tetrahydropyran)carboxamides and (1,3-benzodioxol-5-yl)cyclopentane(tetrahydropyran)carboxylates. The synthesized compounds were evaluated for their effects on the cardiovascular system and blood hemodynamics.